Case Report: Experience of a case of cardiac arrest caused by postoperative pulmonary embolism and hepatic rupture induced by cardiopulmonary resuscitation - Yang, Haowen; Li, Yuehong; Peng, Xiongbing; Li, Zhaojun; Liu, Peiwan; Fang, Xingbao (Frontiers in Cardiovascular Medicine, 2025)
Postoperative pulmonary embolism (PE) poses a serious threat to a patient's life. However, cases involving concurrent liver rupture are exceedingly rare. This report describes a case of a patient who experienced cardiac arrest due to PE following lower extremity varicose vein surgery, followed by liver rupture during cardiopulmonary resuscitation (CPR). Under the timely intervention of a multidisciplinary team (MDT), the patient underwent extracorporeal membrane oxygenation (ECMO)-assisted resuscitation and hepatic repair surgery. Through a staged anticoagulation strategy, a balance was achieved between bleeding control and thrombosis prevention. Ultimately, after 23 days of treatment, the patient regained consciousness and was transferred to rehabilitation.